2018
DOI: 10.3389/fphar.2018.00537
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylene From Dendropanax morbifera Alleviates Diet-Induced Obesity and Hepatic Steatosis by Activating AMPK Signaling Pathway

Abstract: The extract tea of Dendropanax morbifera is popular beverages in Korea, and their preventive and therapeutic roles in metabolic disorders have been reported. However, the molecular mechanism has not been studied despite the known efficacy of D. morbifera. Eleven fractions (fr.1–fr.11) were divided by MPLC to find the active compound. Among them, Fr.5 was superior to others in that the inhibitory efficacy of de novo triglyceride (TG) biosynthesis. NMR analysis revealed that Fr.5 is composed 98% or more (9Z,16S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…DMW-1 and 2 are polyacetylenebased compounds with similar structures (Figure 3), and their structural explanations are provided in the supplementary data ( Supplementary Figures S2 and S3 and Table S1). Of all polyacetylene-based compounds, several studies have reported that (9Z,16S)-16-hydroxy-9,17-octadecadiene-12,14-diynoic acid has anti-obesity, anti-osteoclastogenic, antioxidant, antiinflammatory, and anticomplement activities (Park et al, 2004;Kang et al, 2018;Kim et al, 2018a). The beneficial effect of (2Z, 8Z)-matricaria acid methyl ester has been reported to inhibit tyrosinase activity (Luo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…DMW-1 and 2 are polyacetylenebased compounds with similar structures (Figure 3), and their structural explanations are provided in the supplementary data ( Supplementary Figures S2 and S3 and Table S1). Of all polyacetylene-based compounds, several studies have reported that (9Z,16S)-16-hydroxy-9,17-octadecadiene-12,14-diynoic acid has anti-obesity, anti-osteoclastogenic, antioxidant, antiinflammatory, and anticomplement activities (Park et al, 2004;Kang et al, 2018;Kim et al, 2018a). The beneficial effect of (2Z, 8Z)-matricaria acid methyl ester has been reported to inhibit tyrosinase activity (Luo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Dendropanax morbifera is a subtropical evergreen tree species that is also distributed in other regions of North-East Asia, such as China and Japan. Previous studies have shown that D. morbifera leaf extracts (DMLE) are enriched with polyphenolic compounds that offer a diverse array of functionalities, including antioxidant, anti-inflammatory, anti-obesity, and anti-cancer activities, as well as immunoregulatory functions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that D . morbifera extract was effective in attenuating the inflammatory response [19,20,21]. As demonstrated in Figure 6, levels of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 were significantly increased in the CDDP-treated group, with a 1.5-fold induction in the levels of these cytokines.…”
Section: Resultsmentioning
confidence: 99%